Profil Perceived Academic Stress pada Mahasiswa - Damajanti Kusuma Dewi; Siti Ina Savira; Yohana Wuri Satwika; Riza Noviana Khoirunnisa (Universitas Negeri Surabaya, 2022)
Abstrack : Every human being has experienced a depressed condition commonly known as stress. In psychology, stress is considered as a psychological symptom that afflicts all professions, including students. This study aims to determine the profile of academic stress felt by students at the State University of Surabaya. The research subjects in this study were students of the Faculty of Education, consisting of eight majors, totaling 487. The Perception of Academic Stress Scale (PASS) instrument from Bedewy and Gabriel (2015), was used after going through the adaptation process first. Data were analyzed using descriptive statistics to determine the frequency of each level of perceived academic stress. Based on the results of the analysis showed that as many as 12 students or 2% of the population were in the category of very high academic stress; as many as 136 students or 28% of the population are in the category of high academic stress; as many as 239 students or 49% of the population are in the category of moderate academic stress; as many as 80 students or 16% of the population are in the category of low academic stress; and as many as 20 students or 4% of the population are in the category of very low academic stress. Setiap manusia pernah mengalami kondisi tertekan yang biasa disebut dengan stres. Dalam psikologi, stres dianggap sebagai gejala psikologi yang menimpa pada semua profesi, termasuk mahasiswa. Penelitian ini bertujuan untuk mengetahui profil stres akademik yang dirasakan pada mahasiswa Universitas Negeri Surabaya. Subjek penelitian dalam penelitian ini adalah mahasiswa Fakultas Ilmu Pendidikan, yang terdiri dari delapan jurusan, berjumlah 487. Instrumen Perception of Academic Stress Scale (PASS) dari Bedewy dan Gabriel (2015), digunakan setelah melalui proses adaptasi terlebih dahulu. Data dianalisis menggunakan statistik deskriptif untuk menentukan frekuensi setiap tingkat stres akademik yang dirasakan. Berdasarkan hasil analisis menunjukkan bahwa sebanyak 12 siswa atau 2% dari populasi berada dalam kategori stres akademik yang sangat tinggi; sebanyak 136 siswa atau 28% dari populasi berada dalam kategori stres akademik yang tinggi; sebanyak 239 siswa atau 49% dari populasi berada dalam kategori stres akademik yang dirasakan sedang; sebanyak 80 siswa atau 16% dari populasi berada dalam kategori stres akademik yang rendah; dan sebanyak 20 siswa atau 4% dari populasi berada dalam kategori stres akademik yang sangat rendah.